Peningkatan Resiliensi Badan Usaha Milik Desa Merespon Dampak Pandemi Covid-19 - Hudayana, Bambang; Kutanegara, Pande Made; Fauzanafi, Muhammad Zamzam; Purbawisesa, Angie; Rakryan W D Ulhaq (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2022)
The COVID-19 pandemic has impacted the decline in tourism activities, both those managed by companies, individuals, villages, and Village-Owned Enterprises (BUMDes). The decline in tourism activities has had a secondary impact on small-scale businesses related to the tourism sector. The heavy dependence on the tourism sector and limited other business opportunities have hit the tourism industry's economy hard. Therefore, efforts are needed to enable them to survive and rise from the downturn in these activities. As one of the institutions that carry the Tri Darma of Higher Education, the campus world should have moved to carry out community service dharma. With community service, empowerment programs can be carried out for BUMDes and these business actors to increase resilience. The empowerment program is carried out as (1) workshop facilitation support and discussions with BUMDes managers and business actors in mapping problems and (2) formulating an action plan to reduce the impact and economic recovery of the COVID-19 pandemic. This empowerment program succeeded in mapping out problems and action plans to increase economic resilience during a pandemic and economic recovery through developing multiple economic businesses, such as preserving the tourism business while advancing farming, animal husbandry, mushroom cultivation, and herbal home industries. ==== Pandemi Covid-19 telah berdampak pada merosotnya aktivitas pariwisata baik yang dikelola oleh perusahan, perorangan, desa dan juga Badan Usaha Milik Desa (BUMDes). Kemerosotan kegiatan pariwisata membawa dampak ikutan terhadap usaha skala kecil yang terkait dengan sektor pariwisata. Ketergantungan yang besar terhadap sektor pariwisata dan keterbatasan peluang usaha lain telah memukul perekonomian pelaku wisata secara telak. Oleh karena itu, diperlukan upaya-upaya yang memungkinkan mereka tetap survive dan bangkit dari keterpurukan aktivitas tersebut. Dunia kampus sebagai salah satu institusi yang mengusung Tri Darma Perguruan tinggi sudah semestinya bergerak untuk melakukan darma pengabdian kepada masyarakat. Dengan pengabdian pada masyarakat dapat dilaksanakan program pemberdayaan bagi BUMDes dan pelaku usaha tersebut agar dapat meningkatkan resiliensi. Program pemberdayaan dilakukan dalam bentuk dukungan fasilitasi workshop dan diskusi pengelola BUMDes dan pelaku usaha dalam melakukan pemetaan masalah, dan perumusan rencana aksi untuk mengurangi dampak dan pemulihan ekonomi pandemi Covid-19. Program pemberdayaan ini berhasil memetakan masalah, dan rencana aksi untuk peningkatan resiliensi ekonomi pada masa pandemi dan pemulihan ekonomi melalui pengembangan usaha ekonomi ganda, seperti melestarikan usaha di pariwisata sambil memajukan usaha tani, peternakan, budidaya jamur dan industri rumah tangga herbal.